Opium use and subsequent incidence of cancer: results from the Golestan Cohort Study - Mahdi Sheikh, MD; Ramin Shakeri, PhD; Hossein Poustchi, PhD; Akram Pourshams, ProfMD; Arash Etemadi, PhD; Farhad Islami, PhD; Masoud Khoshnia, MD; Abdolsamad Gharavi, MD; Gholamreza Roshandel, PhD; Hooman Khademi, MD; Sadaf G Sepanlou, PhD; Maryam Hashemian, PhD; et al. (Elsevier, 2020)
Summary: Background: Evidence is emerging for a role of opiates in various cancers. In this study, we aimed to investigate the association between regular opium use and cancer incidence. Methods: This study was done in a population-based cohort of 50 045 individuals aged 40-75 years from northeast Iran. Data on participant demographics, diet, lifestyle, opium use, and different exposures were collected upon enrolment using validated questionnaires. We used proportional hazards regression models to estimate hazard ratios (HRs) and corresponding 95% CIs for the association between opium use and different cancer types. Findings: During a median 10 years of follow-up, 1833 participants were diagnosed with cancer. Use of opium was associated with an increased risk of developing all cancers combined (HR 1·40, 95% CI 1·24-1·58), gastrointestinal cancers (1·31, 1·11-1·55), and respiratory cancers (2·28, 1·58-3·30) in a dose-dependent manner (ptrend<0·001). For site-specific cancers, use of opium was associated with an increased risk of developing oesophageal (1·38, 1·06-1·80), gastric (1·36, 1·03-1·79), lung (2·21, 1·44-3·39), bladder (2·86, 1·47-5·55), and laryngeal (2·53, 1·21-5·29) cancers in a dose-dependent manner (ptrend<0·05). Only high-dose opium use was associated with pancreatic cancer (2·66, 1·23-5·74). Ingestion of opium (but not smoking opium) was associated with brain (2·15, 1·00-4·63) and liver (2·46, 1·23-4·95) cancers in a dose-dependent manner (prend<0·01). We observed consistent associations among ever and never tobacco users, men and women, and individuals with lower and higher socioeconomic status. Interpretation: Opium users have a significantly higher risk of developing cancers in different organs of the respiratory, digestive, and urinary systems and the CNS. The results of this analysis show that regular use of opiates might increase the risk of a range of cancer types. Funding: World Cancer Research Fund International, Cancer Research UK, Tehran University of Medical Sciences, US National Cancer Institute, International Agency for Research on Cancer.